Short-term outcome of physiotherpy and surgical treatment of obstetrical brachial plexus palsy - Krishna Priya Das; Rumpa Mani Chowdhury; Sk. Murad Ahmed; Md. Moniruzaman; Mohammod Shahidullah (Bangabandhu Sheikh Mujib Medical University Journal)
Background: Birth injury to the brachial plexus is referred to as obstetric brachial plexus palsy (OBPP). This study aimed to evaluate the clinical presentation and treatment outcomes of OBPP.